The concept of gambling business in the criminological dimension - Vasylieva, D. O.; Васильєва, Д. О. (Visegrad journal on human rights. – 2019. – № 5 (Vol. 2). – P. 32-37, 2019)
Здійснено узагальнення й аналіз термінології, що використовується для позначення протиправних явищ у сфері ігрового бізнесу. Визначено логіко-формальні аспекти співвідношення грального бізнесу (діяльності, спрямованої на отримання прибутку) й азартних ігор як форми такої діяльності. Розглянуто положення чинного законодавства та проектів законів про детінізацію грального бізнесу. З’ясовано, що розуміння терміна «злочини у сфері грального бізнесу» є занадто широким і формально не визначеним, що залишає можливість зловживань у цій сфері. У межах сфери діяльності, спрямованої на отримання прибутку, виокремлено «законний» і «незаконний» гральний бізнес. Потенційна суспільна небезпека грального бізнесу полягає у використанні такої риси людської психіки, як азарт, що дає змогу отримувати надвеликі злочинні доходи. Зазначено, що гральний бізнес «має право на існування» за умови дотримання спеціальних умов, які б визначалися на рівні нормативно-правого акта. Незаконний гральний бізнес запропоновано розглядати як об’єкт кримінологічного аналізу. Наведено авторське, кримінологічне поняття грального бізнесу з урахуванням положень чинного законодавства. Більш універсальним є визначення незаконного грального бізнесу як зайняття забороненими законом видами діяльності. Здійснення такої діяльності дозволяється законом лише за умови наявності спеціального дозволу – ліцензії.

On the basis of using the methodology of scientific researching the generalization and analysis of the terminology, used to refer the illegal phenomena in the sphere of gambling, have been conducted in the paper. A critical study of the scientific achievements of criminal law and criminology has been accomplished. It was found, that the main part of scientific works, dedicated to the issues of responsibility for gambling had been related to the criminal law characteristics of illegal gambling. Gambling as a type of criminal offense and a separate criminological category until today was not analyzed. Studding gambling business as a subject of a scientific research, permit to determine the logical-formal aspects of an interrelation between gambling business as a profit-oriented activity and gambling as a form of such activity. The provisions of the current legislation and draft laws on the unshadowing of the gambling business are considered. It was concluded, that the understanding of the term of “crimes in the field of gambling” is too large and formally undefined and because of it a possibility for abuse in this area exists. Within the scope of profit-oriented activities, “legitimate” and “illegal” gambling have been distinguished. The potential social danger of the gambling business is what it is based on such a trait of the human psyche as excitement, which allows to obtain extra-large criminal proceeds. It is noted, that gambling business “has the right to exist” in the special conditions, which would be determined at the level of a legal act. The illegal gambling is proposed as an object of the criminological analysis. An original criminological concept, with taking into account the provisions of the current legislation, of gambling business was given in the paper. The most universal understanding of the illegal gambling business is as engaging in activities prohibited by law. Such activity is permitted by law only if there is a special permit – a license.

Осуществлено обобщение и анализ терминологии, используемый для обозначения противоправных явлений в сфере игрового бизнеса. Определены логико-формальные аспекты соотношения игорного бизнеса (деятельности, направленной на получение прибыли) и азартных игр как формы такой деятельности. Рассмотрены положения действующего законодательства и проектов законов о детенизации игорного бизнеса. Выяснено, что понимание термина «преступления в сфере игорного бизнеса» слишком широко и формально не определено, что оставляет возможность злоупотреблений в этой сфере. В рамках сферы деятельности, направленной на получение прибыли, выделен «законный» и «незаконный» игорный бизнес. Потенциальная общественная опасность игорного бизнеса заключается в использовании такой черты человеческой психики, как азарт, позволяющий получать сверхбольшие преступные доходы. Отмечено, что игорный бизнес «имеет право на существование» при соблюдении специальных условий, которые определялись бы на уровне нормативно-правого акта. Незаконный игорный бизнес предлагается рассматривать как объект криминологического анализа. Приведено авторское, криминологическое понятие игорного бизнеса с учетом положений действующего законодательства. Более универсальным является определение незаконного игорного бизнеса как занятие запрещенными законом видами деятельности. Осуществление такой деятельности разрешается законом только при наличии специального разрешения – лицензии.
Поняття грального бізнесу в кримінологічному вимірі
Vasylieva, D. The concept of gambling business in the criminological dimension / Dariia Vasylieva // Visegrad journal on human rights. – 2019. – № 5 (Vol. 2). – P. 32-37.
Keywords: Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; publikatsii u zarubizhnomu vydanni; азартні ігри; gambling; азартные игры; гемблінг; гемблинг; гральний бізнес; gambling business; игорный бизнес; заборона грального бізнесу; prohibition of gambling business; запрет игорного бизнеса; протидія злочинності; crime prevention; противодействие преступности